Cicero's Law Rethinking Roman Law of the Late Republic - du Plessis, Paul J. (Edinburgh University Press, 2016)
This volume brings together an international team of scholars to debate Cicero's role in the narrative of Roman law in the late Republic - a role that has been minimised or overlooked in previous scholarship. This reflects current research that opens a larger and more complex debate about the nature of law and of the legal profession in the last century of the Roman Republic.